Indigenous struggle with mathematics edu-cation in the New Zealand context: from neo-liberal ontology to Indigenous, urban ontologies? - Tweed B (Texas A & M University, 2021)
In this article, the learning of conventional curriculum mathematics in one Indigenous Māori school in Aotearoa/New Zealand is conceptualized as a site of ontological struggle. The major finding of a research project which analyzed extensive ethnographic data gathered in partnership with this school identified an ontological disjunction between curriculum mathematics education and the ethos of the school. This disjunction can be related to the complex and emergent phenomenon in Aotearoa/New Zealand of Indigenous schools in neoliberal, capitalist urban conditions. Centering the ontological commitments of the Māori school challenges the ontological hegemony of curriculum mathematics education and points to a consideration of the possibilities of forms of contemporary mathematical education based on Indigenous ontologies. Embedded in the discussion is a consideration of the ethical position of non-Indigenous researchers working in Indigenous contexts.
(c) The Author